Penerapan Minimum Charge Untuk Outside Guest Restoran Di Amanjiwo Resort - Niken Prihandini (STIE Pariwisata API Yogyakarta, 2019)
Food and beverage service department plays an important role in the hotel’s operational and income’s continuity. In food and beverage service department, restaurant is a center place for arrival of the guests, therefore a waiter or waitres should have an attitude and good service to treat and welcome them. Amanjiwo is ones of a luxurious resort which gives a memorial and prestige service for everyone who comes to Amanjiwo. Because Amanjiwo is private resort and hotels, so they apply minimum spend for non staying or non resident guests to make sure the guests privacy and to keep the luxurious of the hotel. Therefore Amanjiwo apply a minimum charge policy for all outside guests whowould like to enjoy the hotel facilities. The reason why they applied because to many outside guests who come to Amanjiwo just walking around and taking a pictures, someof them make a noise and seated everywhere without spend to buy a meals or beverage. This researched is using descriptive qualitative method by interviewing and observation to several employees about minimum charge at restaurant by seeing how to the service to all the outside guests and its impact to Amanjiwo. With the minimum charge policy applied, it was running smoothly. The hotels can maintained and keep the in house guests privacy. And the hotel revenue is increasing with this minimum charge policy.